Bulgaria, the Jews, and the Holocaust : On the Origins of a Heroic Narrative. - Ragaru, Nadège. (Rochester Studies in East and Central Europe Series, 2023)
A profoundly original historical inquiry, this work offers a critical reflection on the silences of the past and the remembrance of the Holocaust.